Effect of the Concentration of Added Sugar on Organoleptic Properties of Mangrove Syrup from Sonneratia alba fruit - Wintah Wintah; Kiswanto Kiswanto; Afwa Hayuningtyas; Nurdin Nurdin (J-Kesmas: Jurnal Fakultas Kesehatan Masyarakat (The Indonesian Journal of Public Health), 2022)
Mangroves are ecosystems in coastal areas that economically have excellent benefits derived from wood, seeds, and fruit. The most frequently used mangrove fruit as a food source is Sonneratia alba fruit, and Sonneratia alba fruit can be used to produce mangrove syrup. This study aimed to determine the effect of sugar on the organoleptic properties of Mangrove syrup from Sonneratia alba fruit. The organoleptic test method used a hedonic test (preference test) using a rating scale of 1 (dislike very much), 2 (dislikes), 3 (neutral), 4 (likes), and 5 (preferences very much). The treatment P3 (Sonneratia alba 60%: Sugar 40%) was the most highly rated in the quality of taste, color, and aroma, while the most ordered texture quality by the panelists was treatment P2 (Sonneratia alba 40%: sugar 60%).